Gender, Decision Making, and Natural Resource Co-management in Yukon - Staples, Kiri; Natcher, David C. (ARCTIC, 2015)
Across the Canadian North, resource co-management has become a central institution for the management of natural resources. Although many multidisciplinary studies have examined the various social and political dimensions that influence the effectiveness of resource co-management, little has been done to understand how gender might affect collaboration and decision making. This gap is particularly evident in the northern Canadian context, where women make up 16% of all current co-management board members. This study examines the relationship between gender and decision making, drawing on the experiences of those involved in co-management boards in Yukon. Our findings indicate that the representation of women within these institutions is important for establishing a holistic decision-making process and a positive institutional culture that facilitates effective decision making. While there were many different experiences with gender, co-management, and decision making, it was generally agreed that male and female board members had equal opportunities to participate in board decision making. Nonetheless, barriers remain that prevent board members from feeling comfortable acting upon these opportunities. These barriers to participation were experienced by men and women in distinct ways. Institutional level barriers—cases where women’s skills and knowledge were considered irrelevant to co-management, where their opinions lacked standing within decision making—will be the most challenging for co-management boards to address in regard to effective decision making. À l’échelle du Nord canadien, la cogestion des ressources est dorénavant une institution centrale pour assurer la gestion des ressources naturelles. De nombreuses études disciplinaires se sont penchées sur les dimensions sociopolitiques qui influent sur la cogestion des ressources. Cependant, peu d’études ont été réalisées pour comprendre en quoi le sexe de la personne exerce une influence sur la collaboration et la prise de décisions. Cet écart est ...